RESTORATION OF SEISMIC PARAMETERS AND ELECTRICAL CONDUCTIVITY BY THE DIFFRACTION TOMOGRAPHY METHOD - Troyan V.; Kiselev Yu.; Hayakawa M. (My University, 2006)
The results of numerical simulation on restoration of the local elastic inhomogeneities and the local perturbations of electrical conductivity are considered. The restoration is implemented by the diffraction tomography method with the help of elastic and electromagnetic sounding wavefields. The perturbations of electrical conductivity are restored by “diffusive” electromagnetic field. In both cases, seismic and electromagnetic, the direct problem is solved by the finite difference method and the restoration is implemented in the time domain using the first order Born approximation.